House Of Baking Supplier (Supply Halal Bakery Ingredients) / Ammar Umairul Sabri Mat Nawi ... [et al.] - Ammar Umairul, Sabri Mat Nawi; Muhammad Azim Mubaraq, Mhd Azhari; Nur Balqis, Zainun Abiden; Siti Ili Maisarah, Mat Kamil (2019)
First of all, The purpose of this report is to provide an overview of the business we have undertaken and the businesses that have been taken into account by us before commencing business. not only that we also want to make sure that our business is on par with other entrepreneurs and even more so can satisfy our customers. So, this is summary information about our busniess. The name given for our company is "House Of Baking Supplier" because our business is selling bakery ingredients besides taking further orders to free delivery to our customers. This is a special offer given to customers as well as the supplied bakery ingredients are halal and clean from harmful chemicals. House Of Baking Supplier is a company we actively established and own by the partnership. Since we started our business on a small scale as a starter and just have a premise for processing the product with our own recipe like chocolate flavor and carry out management activities. As in this case, we need to produce product or bakery ingredients with good quality,halal and clean because this is our specialist from other bakery supplier . So that our companies to be main focus for customers to come to our shop and provide excellent bakery ingredients to our customers by supplying our products according to demand. We chose this business because we want to give something new to our customers through our products or bakery ingrdients already existing now. On the other hand, we want a return to double profit every request from customers. Future, we hope to have a processing plan larger products and opening several branches in other states in Malaysia and overseas. From the name of company , automically we can know what kind of business is running is we as supplier to bakery ingredients like various flavor of flavour , flavoring, oil and shortening, dairy and milk and so on. We also give discount to our customer if they buy with large amount or quantity of bakery ingredients and providing free delivery for every purchase. We also provide several of marketing strategic to increase and developing our busniess not only in Malaysia but also in overseas. The marketing strategic used is media massa and advertisement especially like facebook, instagram, twitter, email, and others. This is very important so that our business can be recognized by the public in whole the world in addition can increasing the quantity of demand for our products and can gain more profit monthly.